2020
DOI: 10.1111/bjc.12244
|View full text |Cite
|
Sign up to set email alerts
|

Preventing relapse with personalized smart‐messaging after cognitive behavioural therapy: A proof‐of‐concept evaluation

Abstract: Objectives. Cognitive behavioural therapy (CBT) can improve symptoms of anxiety and depression, but also reduces the risk of future relapse after therapy completion. However, current CBT relapse prevention methods are resource-intensive and can be limited in clinical practice. This paper investigates a personalized means of reducing relapse using smart-messaging in two settings: research and routine care.Design. Study 1 presents a cohort study comparing a cohort of smart-messaging users versus non-users. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Based on our findings, the communication media used to administer internet-facilitated interventions to patients can be classified into three categories: web apps, mobile apps, and computer games. A significant number of the included studies were based on web apps [ 11 , 14 , 24 , 39 , 43 , 49 , 50 , 52 , 54 , 56 , 63 ], followed by mobile apps [ 13 , 32 , 41 , 49 , 50 , 55 , 60 , 61 ] and a game-based intervention [ 53 ]. There was only one paper that applied both web and mobile technologies for internet-based intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our findings, the communication media used to administer internet-facilitated interventions to patients can be classified into three categories: web apps, mobile apps, and computer games. A significant number of the included studies were based on web apps [ 11 , 14 , 24 , 39 , 43 , 49 , 50 , 52 , 54 , 56 , 63 ], followed by mobile apps [ 13 , 32 , 41 , 49 , 50 , 55 , 60 , 61 ] and a game-based intervention [ 53 ]. There was only one paper that applied both web and mobile technologies for internet-based intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Another notable observation is that several studies (11/31, 35%) used feedbacks as adaptive elements. Numerous studies described the process of adaptive feedback in different forms, including sending personalized motivational messages [ 43 ], tailored messages by therapists [ 11 , 13 , 54 ], and providing general support [ 14 ]. In contrast, a few studies aimed to adapt reminders and alerts by sending an email or SMS text message or making a phone call [ 24 , 48 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the rst randomised-controlled trial to investigate the clinical utilities of a 'Simple-Telehealth' (Florence) text-messaging technology to assist the mental health care of patients with severe and enduring mental illness. Preliminary evidence from small cohort and case studies suggest that "Florence is a low-cost, low-risk innovation with a strong track record" [30]; studies reported bene ts on self-management, recovery outcomes and treatment adherence, predominantly in the management of physical long-term conditions such as hypertension and diabetes [31], but also more recently for patients with mental health problems following psychotherapy [32]. Other studies provided preliminary evidence for the effectiveness of more complex text-messaging interventions that incorporated Cognitive Behaviour Therapy techniques to target medication adherence and psychotic symptoms [33] or used an 'Early Warning Signs Questionnaire' for relapse prevention [34].…”
Section: Discussionmentioning
confidence: 99%
“…Personalised, targeted smart messaging may improve retention in psychological therapy and outcomes after the completion of therapy. 36 37 Therefore, relapse prevention plans will be organised into brief weekly reminders that can be sent as text messages after therapy has finished. The messages received will be tailored to participant-reported well-being each week, with messages specific to times when they are doing well, experiencing early warning signs of relapse or experiencing full relapse.…”
Section: Methodsmentioning
confidence: 99%